THE AFFECT OF PERSONAL CHARACTERISTICS, MOTIVATION AND WORK DISCIPLINE AGAINST EMPLOYEE PERFORMANCE - Santi Maodia Fathonah; Kasmir Kasmir (Dinasti Publisher, 2021)
This research aims to investigate further regarding those influence which come from personal characteristics, motivation and work discipline towards employee performance at PT Hi-Lex Cirebon. The research population was employees from PT Hi-Lex Cirebon, with a total sample of 103 employees. The research method used a quantitative method. The data were processed through Structural Equation Model-Partial Least Square (SEM-PLS) analysis by SmartPLS 3.2.7 software. The results showed that the personal characteristics had a positive influence on employee performance, motivation had none relate to employee performance and work discipline had a positive influence on employee performance.